Ugandan hotel employee innovativeness: the role of transformational leadership and cultural intelligence - Kisubi, Moses Kisame; Mukyala, Veronica; Namono, Rehema (Emerald, 2025)
Purpose This study aims to determine the indirect influence of transformational leadership on cultural intelligence and employee innovativeness in the context of Ugandan hotel employees. Design/methodology/approach We employed a cross-sectional correlational design to collect and analyze data from 285 hotel employees. We tested for the mediation effect of cultural intelligence in the relationship between transformational leadership and employee innovativeness using Hayes’ PROCESS macro version 4.2 model 4. Findings The findings indicate a positive relationship between transformational leadership, cultural intelligence and employee innovativeness. Results further indicate that cultural intelligence partially mediates the relationship between transformational leadership and employee innovativeness. Research limitations/implications Empirically, we add to the existing findings that have established a positive relationship between cultural intelligence, transformational leadership and employee outcomes. More insightfully, results provide evidence of the indirect role of transformational leadership in this relationship. Practically, since hospitality is a multicultural setting, employees with high cultural intelligence adjust quickly as they interact with guests from different cultures. Originality/value The study established the mechanisms under which transformational leadership influences the relationship between cultural intelligence and employee innovativeness.